COMPARATIVE STUDIES ON TRENDS AND STRATEGIES FOR COMBATING CYBERCRIME BETWEEN INDONESIA AND DEVELOPED COUNTRIES - Muhammad Ahfadh Fazlurrohman; Surya Nita; Muhammad Erza Aminanto (Transpublika Publisher, 2024)
Cybercrime has become a significant global threat, targeting individuals, organizations, and governments with increasing sophistication. This study aims to conduct a comparative analysis of cybercrime trends, patterns, and mitigation strategies between Indonesia and developed countries. Using a Systematic Literature Review (SLR) method, this research highlights the dominance of phishing and ransomware in Indonesia, often exploiting weak digital literacy and regulatory gaps. Conversely, advanced threats like Advanced Persistent Threats (APT) and AI-based malware are prevalent in developed countries, supported by robust cybersecurity infrastructure and international regulations such as the Budapest Convention. The findings emphasize the urgent need for Indonesia to enhance its cybersecurity readiness through technology adoption, legal framework improvement, and public education. This study offers valuable insights into bridging the cybersecurity gap between developing and developed nations, promoting international collaboration for a safer digital ecosystem. Adopting more modern strategies can be an opportunity for Indonesia to enhance its cyber resilience.